Dubai Electricity and Water Authority (DEWA): a case study on sustainability - Amjad Suri; Abdullah Al-Hadrami; Adel Sarea; Ali ElAsad (Journal of Business and Socio-Economic Development)
Purpose – The main purpose of the Dubai Electricity and Water Authority (DEWA) sustainability case is to allow students to explore how nonfinancial information reported in sustainability plays a vital role in maintaining a trade-off between current economic pressure and future environmental needs. Design/methodology/approach – This is an exploratory study in nature using a qualitative case study approach. The case requires an examination of DEWA's sustainability reporting (SR) in the context of Global Reporting Initiatives (GRIs). This case is designed to assist students in gauging DEWA's sustainability and explore how the company evaluates the materiality of sustainability issues. Findings – With stakeholders' and investors' increased interest in sustainability, the authors argue that accounting programs should incorporate this topic into their curricula. The case enables students to focus on sustainability-related initiatives with DEWA that are aligned with GRI initiatives. The case might be instructive for both undergraduate and postgraduate students studying environmental and management accounting. Originality/value – This case study is the first of its kind in the Gulf Cooperation Council (GCC) region to comprehensively analyze DEWA's sustainability practices concerning GRI-based SR. This study widens the understanding of DEWA's implementation of GRI standards in the preparation of its sustainability reports.